Career Guidance Efficacy in Secondary Education: Workforce Preparedness Analysis - Krishna, Gauri; Rangaswamy, Rashmi (Journal of Educational Research and Policies, 2026)
Career guidance programs are increasingly recognized as essential tools for equipping students with the skills and knowledge necessary to navigate future employment landscapes. This study highlights the increasing importance of such programs, especially in India, where rapid societal and economic changes necessitate well-prepared graduates. This qualitative case study explores the structure, implementation, and outcomes of a career guidance program at a secondary school The study aims to understand stakeholder perceptions, identify program strengths and weaknesses, and suggest improvement areas. Participants include students, teachers, parents, counsellors, and school administrators. Data collection methods involve document analysis, semi-structured interviews, focus groups, and observations. The research examines the program's effectiveness in preparing students for career decision-making and identifies key factors influencing its success. Areas explored include program structure, stakeholder perceptions, strengths, challenges, and recommendations for improvement.